Pyrolytic ultra-thin silicon nitride ceramic substrate and preparation method thereof
Patent Information
- Application Number
- CN202611221159.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]然而,现有技术中氮化硅陶瓷基板仍存在以下不足:(1)制备过程中陶瓷浆料因有机含量高,浆料流变性不足以支撑超薄生带的流延均一性,且排胶过程收缩大,抗形变能力弱;(2)传统流延热风干燥带来生瓷带上下面溶剂挥发速率不一致,薄坯体因干燥速率不均产生卷曲、褶皱、微裂纹缺陷;(3)传统敷粉堆叠方式,无法满足即烧型超薄氮化硅基板的外观控制要求;(4)现有0.200 mm以下规格超薄氮化硅陶瓷基板主流制备工艺,以大厚度基板通过双面研磨加工为主,成品尺寸多局限于2英寸左右,难以适配市场对大尺寸超薄氮化硅基板的应用需求;同时研磨加工易造成基板表层损伤,破坏氮化硅晶粒完整结构,使基板形成原生微观缺陷
[0066](1)本发明针对超薄流延坯体干燥收缩大、易开裂、生坯强度低、脱脂产气集中、坯体易穿孔塌陷的痛点,采用粗细双峰亚微米氮化硅粉体复配体系,有效提升浆料固含量、降低成型收缩率。
Smart Images

Figure CN123003298A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor ceramic substrate technology, specifically relating to an instant-fired ultrathin silicon nitride ceramic substrate and its preparation method. Background Technology
[0002] Silicon nitride ceramic substrates, with their excellent insulation properties, high thermal conductivity, and good chemical stability, have been widely used in the field of electronic packaging. The core advantage of ultra-thin silicon nitride ceramic substrates in AI chips and new energy sectors lies in the synergistic unity of thermal resistance compression and mechanical strength support achieved through extreme thinness. This simultaneously meets the kilowatt-level heat dissipation requirements of AI computing chips and the thermal shock resistance reliability requirements of SiC modules for 800V platforms in new energy, making it the only systematic ceramic substrate solution that combines high thermal conductivity (>80 W / m·K), high bending strength (≥900MPa), and low dielectric loss.
[0003] In the field of chip-level heat dissipation, for high-performance CPUs, GPUs, NPUs, and ASICs (especially AI chips), silicon nitride ceramic substrates can be used as ultra-thin heat dissipation sheets that are directly attached to the back of the chip without an interface layer. These heat dissipation sheets are less than 0.100 mm thick and have extremely low thermal resistance, thus overcoming the heat dissipation bottleneck introduced by the interface layer in traditional thermal pads or thermal greases. Simultaneously, they possess high flexural strength, ensuring the structural integrity of the substrate under complex working environments and mechanical stress, preventing failures such as breakage.
[0004] However, existing silicon nitride ceramic substrates still have the following shortcomings: (1) Due to the high organic content of the ceramic slurry during the preparation process, the slurry rheology is insufficient to support the uniformity of the ultrathin green tape, and the shrinkage during the glue removal process is large, resulting in weak resistance to deformation; (2) Traditional hot air drying of the green ceramic tape leads to inconsistent solvent evaporation rates on the upper and lower surfaces, and the thin blank produces curling, wrinkling, and microcrack defects due to uneven drying rates; (3) Traditional powder stacking methods cannot meet the appearance control requirements of the instant-fired ultrathin silicon nitride substrate; (4) The current mainstream preparation process for ultrathin silicon nitride ceramic substrates with specifications below 0.200 mm mainly involves double-sided grinding of thick substrates, and the finished product size is mostly limited to about 2 inches, which is difficult to adapt to the market's application demand for large-size ultrathin silicon nitride substrates; at the same time, grinding processing is prone to damage to the substrate surface, destroying the complete structure of silicon nitride grains and causing the substrate to form native micro-defects. Such defects continue to expand and deteriorate under the coupling effect of subsequent service stress and complex environment, significantly reducing the long-term reliability and service life of the substrate.
[0005] Therefore, how to prepare an instant-fired ultrathin silicon nitride ceramic substrate is a problem to be solved. Summary of the Invention
[0006] This invention aims to provide an ultrathin, high thermal conductivity silicon nitride ceramic substrate and its preparation method. Through synergistic innovation in material system, molding structure and green body stacking, it achieves the production of silicon nitride ceramic sheets with a thickness ≤0.200mm, thermal conductivity ≥80W / (m·K), and bending strength ≥900MPa.
[0007] To address the above problems, this invention provides a method for preparing an instant-fired ultrathin silicon nitride ceramic substrate, comprising the following steps:
[0008] A. Slurry preparation: 50-65 parts by weight of compounded silicon nitride powder, 5-10 parts by weight of composite sintering aid, 0.5-3 parts by weight of dispersant, 13-25 parts by weight of organic solvent, 7-12 parts by weight of biodegradable bio-based polymer binder, and 2-7 parts by weight of plasticizer are ball-milled to obtain silicon nitride slurry; the compounded silicon nitride powder is a mixture of fine-particle-size powder (0.2-0.5 μm) and medium-particle-size powder (0.6-0.9 μm) at a mass ratio of 3-7:7-3; the composite sintering aid is a mixture of sintering aid A and sintering aid B, where sintering aid A is at least one of magnesium oxide, lanthanum oxide, yttrium oxide, aluminum oxide, gadolinium oxide, or lutetium oxide, and sintering aid B is at least one of magnesium silicon nitride or yttrium silicon carbonitride; the dispersant is a modified styrene-maleic anhydride copolymer.
[0009] B. Casting: After adjusting the viscosity of the silicon nitride slurry, casting is performed. After completion, the upper and lower surfaces are pre-crosslinked and cured using an ultraviolet light source. After completion, segmented gradient low-temperature drying is used. The drying temperature is divided into multiple segments, gradually increasing from 30±3℃ to 80±5℃. The cast green ceramic tape flows through each temperature zone and is die-cut to obtain the green body.
[0010] C. Glue Removal: Select N+1 sheets of graphite paper, coat both sides of N-1 sheets of graphite paper and one side of 2 sheets of graphite paper with a boron nitride coating, and alternately stack N green blanks with N+1 sheets of graphite paper, ensuring that the upper and lower layers of the green blanks are both graphite paper, and that the contact surfaces between the green blanks and the graphite paper have a boron nitride coating, and perform glue removal to obtain glue-removed blanks; N is an integer greater than or equal to 1;
[0011] D. Sintering: The blank is subjected to gas pressure sintering under an inert atmosphere to obtain an instant-fired ultrathin silicon nitride ceramic substrate.
[0012] Preferably, in the above preparation method, in step A, the sintering aid A is at least two of magnesium oxide, lanthanum oxide, yttrium oxide, aluminum oxide, gadolinium oxide, or lutetium oxide.
[0013] In the above preparation method, in step A, sintering aid A accounts for 40% to 80% of the total sintering aid mass, and sintering aid B accounts for 20% to 40% of the total sintering aid mass.
[0014] In the above preparation method, in step A, the particle size of sintering aid A is 0.05~0.5μm.
[0015] In the above preparation method, in step A, the particle size of sintering aid B is 0.8~1.5μm.
[0016] In the above preparation method, in step A, the organic solvent is a mixture of benzene and alcohol, wherein the benzene is at least one of benzene, toluene, xylene or trimethylbenzene, and the alcohol is at least one of methanol, ethanol, propanol, butanol, pentanol or hexanol.
[0017] Preferably, in the above preparation method, in step A, the organic solvent is a low-toxicity azeotropic system of benzene and alcohol in a mass ratio of 2~8:8~2.
[0018] More preferably, in the above preparation method, in step A, the organic solvent is a mixture of ethanol and at least one of toluene or xylene in a mass ratio of 2~8:8~2.
[0019] In the above preparation method, in step A, the modified styrene-maleic anhydride copolymer is a compound of SMA and PPO in a mass ratio of 3~7:7~3.
[0020] In the above preparation method, in step A, the biodegradable bio-based polymer binder is at least one of corn starch, cassava starch, methylcellulose, and ethylcellulose.
[0021] Preferably, in the above preparation method, in step A, the biodegradable bio-based polymer binder is at least two of corn starch, tapioca starch, methylcellulose, and ethylcellulose.
[0022] More preferably, in the above preparation method, in step A, the biodegradable bio-based polymer binder is a compound of at least one of corn starch or tapioca starch and at least one of methylcellulose or ethylcellulose.
[0023] Most preferably, in the above preparation method, in step A, the biodegradable bio-based polymer binder is a compound of at least one of corn starch or cassava starch and at least one of methylcellulose or ethylcellulose in a mass ratio of 2~8:8~2.
[0024] In the above preparation method, in step A, the plasticizer is at least one of tetraethyl orthosilicate, PEG400, dioctyl adipate, or diisononyl cyclohexanedicarboxylate.
[0025] In the above preparation method, in step A, silicon nitride ceramic balls occupying 1 / 4 to 1 / 2 of the ball mill volume are added during ball milling.
[0026] In the preparation method described above, in step A, the compounded silicon nitride powder, composite sintering aid, dispersant and organic solvent are first ball-milled, and then a biodegradable bio-based polymer binder and plasticizer are added for a second ball milling.
[0027] Furthermore, in the above preparation method, in step A, the rotation speed of the first ball mill is 80~150 rpm.
[0028] Furthermore, in the above preparation method, in step A, the first ball milling time is 5h~20h.
[0029] Furthermore, in the above preparation method, in step A, the rotation speed of the second ball mill is 80~150 rpm.
[0030] Furthermore, in the above preparation method, in step A, the second ball milling time is 10h~30h.
[0031] In the above preparation method, in step B, the drying temperature is 2 to 4 of the following four temperatures: 30±3℃, 40±3℃, 50±3℃, 60±3℃, and 70±3℃, and 80±5℃.
[0032] In the above preparation method, in step B, the viscosity of the silicon nitride slurry is adjusted to 5000~20000 Pa·s.
[0033] In the above preparation method, in step B, the wavelength of the ultraviolet light source is 360±40nm.
[0034] In the above preparation method, in step B, the pre-crosslinking curing time is 5~30s.
[0035] In the above preparation method, step B involves drying in 4-5 temperature ranges.
[0036] In the above preparation method, in step B, the cast green ceramic tape flows uniformly through each temperature zone at a speed of 1600~2000 mm / h.
[0037] In the above preparation method, in step B, the thickness of the green blank is 0.09~0.25mm.
[0038] In the above preparation method, in step B, the size of the green blank is 248mm × 185mm, and the allowable dimensional deviation is 1%.
[0039] In step B of this invention, a high-precision roll-to-roll casting equipment is used for coating and forming. The casting substrate is a low-stress, micro-embossed PET carrier tape, and the wet film thickness is precisely matched to the green body thickness of 0.09~0.25mm. After casting and coating, the upper and lower surfaces of the green body are immediately subjected to simultaneous UV pre-crosslinking curing for 5~30s using a UV light source. After pre-curing, segmented gradient low-temperature drying is used, with the drying temperature gradually increasing from 30±3℃ to 80±5℃. Solvent is removed slowly in multiple stages, and the cast green ceramic tape flows through each temperature zone to obtain an ultra-thin silicon nitride ceramic green tape (green body). After casting and drying, the ultra-thin silicon nitride ceramic green tape can be cut, stacked, and flattened to obtain an ultra-thin silicon nitride ceramic green body.
[0040] In the above preparation method, in step C, the thickness of the graphite paper is 0.2~1.2 mm.
[0041] In the above preparation method, in step C, the ash content of the graphite paper is ≤300ppm.
[0042] In the above preparation method, in step C, the thickness of the boron nitride coating is 5~15μm.
[0043] In the above preparation method, in step C, the debinding is carried out under an inert atmosphere (e.g., using nitrogen, argon, etc., with nitrogen purity ≥ 99.99%).
[0044] In the above preparation method, during step C, the flow rate of the inert gas during glue discharge is 100~700L / min.
[0045] In the above preparation method, during step C, the ambient oxygen content is 500~800ppm when the adhesive is discharged.
[0046] In the above preparation method, during step C, the ambient air pressure is -5 to -10 Pa when discharging the adhesive.
[0047] In this invention, an ultrathin silicon nitride ceramic green body is formed by alternating layers of graphite paper + green body + graphite paper + green body to create a flexible sandwich constraint structure. This structure is then placed in a double-layer porous boron nitride sandwich plate for adhesive removal.
[0048] In the above preparation method, in step C, during the glue removal process, the room temperature is raised to 220±20℃ and kept at that temperature, then raised to 400±40℃ and kept at that temperature, and then raised to 600±60℃ and kept at that temperature.
[0049] Furthermore, in the above preparation method, in step C, the heating rate from room temperature to 220±20℃ is 1~2℃ / min.
[0050] Furthermore, in the above preparation method, in step C, the temperature is maintained at 220±20℃ for 30~60min.
[0051] Furthermore, in the above preparation method, in step C, the heating rate to 400±40℃ is 0.5~1.5℃ / min.
[0052] Furthermore, in the above preparation method, in step C, the temperature is maintained at 400±40℃ for 60~90min.
[0053] Furthermore, in the above preparation method, in step C, the heating rate to 600±60℃ is 1~2℃ / min.
[0054] Furthermore, in the above preparation method, in step C, the temperature is maintained at 600±60℃ for 60~180min.
[0055] In the above preparation method, in step D, a crucible is used for sintering. The crucible is made of boron nitride and has a porosity of 25-50%.
[0056] In the preparation method described above, in step D, during sintering, the temperature is raised from 20~30℃ to 1100~1300℃ and held at 0.12~0.18MPa, then raised to 1500~1700℃ and held at 0.3~0.55MPa, then raised to 1800~1900℃ and sintered at 0.6~1.0MPa.
[0057] Furthermore, in the above preparation method, in step D, the heating rate from 20~30℃ to 1100~1300℃ is 5~8℃ / min.
[0058] Furthermore, in the above preparation method, in step D, the temperature is maintained at 0.12~0.18MPa for 40~120min.
[0059] Furthermore, in the above preparation method, in step D, the heating rate to 1500~1700℃ is 2~5℃ / min.
[0060] Furthermore, in the above preparation method, in step D, the temperature is maintained at 0.3~0.55MPa for 60~180min.
[0061] Furthermore, in the above preparation method, in step D, the heating rate to 1800~1900℃ is 2~5℃ / min.
[0062] Furthermore, in the above preparation method, in step D, sintering is performed at 0.6~1.0 MPa for 180~500 min.
[0063] In the above preparation method, in step D, the thickness of the obtained sintered ultrathin silicon nitride ceramic substrate is 0.07~0.20 mm. In this invention, the green blank is sintered with binder, and especially during sintering, it shrinks in the length, width, and thickness directions. Therefore, the thickness of the green blank obtained in step B is slightly larger than the thickness of the binder-removed blank obtained in step C, and significantly larger than the thickness of the sintered ultrathin silicon nitride ceramic substrate in step D. Furthermore, since the binder-removed blank is extremely fragile, its thickness is generally not measured.
[0064] This invention also provides an instant-fired ultrathin silicon nitride ceramic substrate, which, prepared by the above-described method, exhibits a flexural strength ≥900 MPa and a thermal conductivity ≥80 W·m. -1 ·K -1 Warpage of 0.1% to 0.3%.
[0065] The beneficial effects of this invention are:
[0066] (1) In view of the pain points of large drying shrinkage, easy cracking, low green strength, concentrated degreasing gas generation, and easy perforation and collapse of the green body, the present invention adopts a coarse and fine bi-peak submicron silicon nitride powder compound system to effectively increase the solid content of the slurry and reduce the molding shrinkage rate.
[0067] (2) This invention abandons the high-shrinkage pure organic system commonly used in traditional silicon nitride casting, which typically employs high-content PVB, polyvinyl alcohol, and phthalic plasticizers. Instead, it creatively adopts a ternary bifunctional low-shrinkage organic system consisting of a biodegradable bio-based binder, a modified ceramic precursor plasticizer, and a low-volatility dispersant. Through precise component matching of the binder, plasticizing, and dispersing phases, it solves the industry pain points of high shrinkage, easy cracking, uneven dispersion, and concentrated gas generation during degreasing in ultra-thin preforms. The organic component content of traditional silicon nitride casting slurry is generally greater than 20 wt%, and the volume shrinkage rate during the debinding and sintering process is as high as 18% or more. This invention constructs a special organic system for ultrathin materials with low shrinkage, gentle gas production, high dispersion, and low residual carbon. It can strictly control the total organic component content of ultrathin silicon nitride slurry to 12~16wt%, reduce the overall volume shrinkage rate during the glue removal stage, significantly reduce the structural strain and internal stress of ultrathin preforms during the glue removal process, and completely solve the core defects such as perforation, blistering, microcracks, and warping deformation caused by severe shrinkage in ultrathin preforms of 0.200mm and below.
[0068] (3) In the casting process, the present invention abandons the traditional single hot air direct drying method and adopts a double-sided ultraviolet in-situ pre-curing + gradient low temperature drying coupling process. The double-sided ultraviolet pre-curing suppresses the stress difference between the upper and lower parts caused by the rapid evaporation of solvent and avoids the ultra-thin blank from curling, wrinkling and micro-crack defects caused by uneven drying rate.
[0069] (4) This invention abandons the traditional preparation process of using thick substrate laser cutting followed by double-sided grinding for ultra-thin silicon nitride ceramic substrates. Instead, it adopts an integrated large-size co-firing process, which can prepare large-size ultra-thin silicon nitride ceramic substrates with a thickness of 0.07~0.20mm and an external size of 190mm×138mm (the thickness and size of the finished product will shrink to a certain extent). Furthermore, it eliminates the need for subsequent grinding processes, thus avoiding surface damage to the intact structure of silicon nitride grains caused by grinding, and significantly improving the long-term reliability and service life of the substrate. Attached Figure Description
[0070] Figure 1 This is a physical image of the sintered ultrathin silicon nitride ceramic substrate of the present invention.
[0071] Figure 2 The image shows a SEM image of the silicon nitride substrate prepared in Example 1.
[0072] Figure 3 The image shows a SEM image of the silicon nitride substrate prepared for Comparative Example 1. Detailed Implementation
[0073] The present invention will be explained below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or in accordance with the product manual.
[0074] Example 1
[0075] S1 Pulping: 60 parts by weight of a compounded silicon nitride powder (0.3~0.4μm fine particle size powder and 0.7~0.8μm medium particle size powder in a mass ratio of 5:5), 8 parts by weight of a mixture of magnesium oxide, yttrium oxide and magnesium silicon nitride (magnesium oxide, yttrium oxide and magnesium silicon nitride in a mass ratio of 3:3:2), 1.5 parts by weight of a modified styrene-maleic anhydride copolymer (SMA and PPO in a mass ratio of 6:4), and 19.5 parts by weight of toluene and anhydrous ethanol (toluene and anhydrous ethanol). Ethanol (mass ratio 3:7) was mixed and placed in a ball mill. 1 / 3 of the ball mill's internal volume of silicon nitride ceramic balls was added. After ball milling at 100 r / min for 10 h, a silicon nitride dispersion slurry was obtained. Then, 10 parts by mass of a biodegradable bio-based polymer binder (ethyl cellulose and cassava starch in a 7:3 ratio) and 3 parts by mass of tetraethyl orthosilicate were added to the silicon nitride dispersion slurry. After ball milling at 120 r / min for 20 h, a silicon nitride slurry was obtained.
[0076] S2 Casting: After adjusting the viscosity of the silicon nitride slurry to 6000~8000 Pa·s, the casting process is carried out. A high-precision roll-to-roll casting machine is used for coating and forming. The casting substrate is a low-stress micro-embossed PET carrier tape. The wet film thickness is precisely matched to the green body thickness of about 0.13mm. After casting and coating, 365nm double-sided UV pre-curing is performed for 10~15s. After pre-curing, the casting machine is set to five temperature zones with five gradient low-temperature drying at 30℃-40℃-50℃-60℃-80℃. The cast green ceramic tape flows uniformly through each temperature zone at a speed of 1800mm / h. After die-cutting, a low-stress ultra-thin green body with a thickness of about 0.13mm is obtained, with a size of about 245 mm × 185 mm.
[0077] S3 Debinding: Eleven sheets of 0.8mm high-purity graphite paper (ash content ≤300 ppm) were selected. A 10μm thick boron nitride coating was applied to both sides of nine sheets of graphite paper and one side of two sheets. Ten green blanks were alternately stacked with graphite paper, ensuring that both the top and bottom layers were graphite paper and that the contact surfaces between the green blanks and graphite paper had a boron nitride coating. This structure was placed in a double-layer porous boron nitride clamp, and nitrogen gas with an oxygen content of 500 L / min and an oxygen content of 500~800 ppm was introduced. The temperature was increased from room temperature to 220℃ at a rate of 1℃ / min and held for 30 min, then increased to 400℃ at a rate of 1.5℃ / min and held for 90 min, and then increased to 530℃ at a rate of 1.5℃ / min and held for 120 min. The furnace pressure was controlled at -5pa throughout the process. Debinding was performed under these conditions to obtain an ultrathin silicon nitride ceramic debinded blank.
[0078] S4 sintering: The crucible material is boron nitride with a porosity of 25%; the grain framework is constructed by heating from 30℃ to 1200℃ at 5℃ / min and holding at low pressure of 0.15MPa for 100min; then the temperature is increased to 1600℃ at 5℃ / min and held at 0.5MPa for 65min; then the temperature is increased to 1850℃ at 2℃ / min and sintered at 0.8MPa for 4h.
[0079] The ultrathin silicon nitride ceramic substrate prepared in Example 1 has a thickness of approximately 0.098 mm, a thermal conductivity of 82.6 W / (m·K), a flexural strength of 926 MPa, a warpage of 0.22%, and a porosity of approximately 0.2%. Its physical image is shown below. Figure 1 As shown; its surface SEM characterization is as follows Figure 2 As shown, there are a large number of long and thick columnar crystal rods with clear and complete outlines and high aspect ratio, which bring strong flexural strength and toughness, making them suitable for various application scenarios. This reflects the compounding of powders with different particle sizes, resulting in the regular arrangement of crystals of different sizes, increasing the friction on the substrate surface, and which is beneficial to the stability of subsequent processes such as copper plating and metallization in the application end.
[0080] Example 2
[0081] S1 Pulping: 60 parts by weight of a compounded silicon nitride powder (0.3~0.4μm fine particle size powder and 0.7~0.8μm medium particle size powder in a mass ratio of 5.5:4.5), 8 parts by weight of a mixture of magnesium oxide, yttrium oxide, and silicon carbonitride yttrium (magnesium oxide, yttrium oxide, and silicon carbonitride yttrium in a mass ratio of 3:3:2), 1.5 parts by weight of a modified styrene-maleic anhydride copolymer (SMA and PPO compounded in a mass ratio of 7:3), and 19.5 parts by weight of toluene and anhydrous ethanol (toluene...). The mixture was placed in a ball mill with anhydrous ethanol at a mass ratio of 3:7. 1 / 3 of the ball mill's internal volume of silicon nitride ceramic balls was added. After ball milling at 100 r / min for 10 h, a silicon nitride dispersion slurry was obtained. Then, 10 parts by mass of a biodegradable bio-based polymer binder (ethyl cellulose and cassava starch compounded in a 5:5 ratio) and 3 parts by mass of tetraethyl orthosilicate were added to the silicon nitride dispersion slurry. After ball milling at 120 r / min for 20 h, a silicon nitride slurry was obtained.
[0082] S2 Casting: After adjusting the viscosity of the silicon nitride slurry to 8000~10000 Pa·s, the casting process is carried out. A high-precision roll-to-roll casting machine is used for coating and forming. The casting substrate is a low-stress micro-embossed PET carrier tape. The wet film thickness is precisely matched to the green body thickness of about 0.240 mm. After casting and coating, it is pre-cured with 365 nm double-sided UV for 15~20 s. After pre-curing, the casting machine is set to five temperature zones with five gradient low-temperature drying at 30℃-40℃-50℃-60℃-80℃. The cast green ceramic tape flows uniformly through each temperature zone at a speed of 2000 mm / h. The die-cutting yields a low-stress ultra-thin green body with a thickness of about 0.240 mm and a size of about 245 mm × 185 mm.
[0083] S3 Debinding: Eleven sheets of 0.8mm high-purity graphite paper (ash content ≤300 ppm) were selected. A 10μm thick boron nitride coating was applied to both sides of nine sheets of graphite paper and one side of two sheets. Ten green blanks were alternately stacked with graphite paper, ensuring that both the top and bottom layers were graphite paper and that the contact surfaces between the green blanks and graphite paper had a boron nitride coating. This structure was placed in a double-layer porous boron nitride clamp, and nitrogen gas with an oxygen content of 500 L / min and an oxygen content of 500~800 ppm was introduced. The temperature was increased from room temperature to 220℃ at a rate of 1.5℃ / min and held for 40 min, then increased to 400℃ at a rate of 1℃ / min and held for 80 min, and then increased to 530℃ at a rate of 1.5℃ / min and held for 120 min. The furnace pressure was controlled at -10 Pa during the process. Debinding was performed under these conditions to obtain an ultrathin silicon nitride ceramic debinded blank.
[0084] S4 sintering: The crucible material is boron nitride with a porosity of 50%; the grain framework is constructed by heating from 30℃ to 1200℃ at 6℃ / min and holding at a low pressure of 0.15MPa for 110min; then the temperature is increased to 1600℃ at 4℃ / min and held at a transition pressure of 0.5MPa for 65min; then the temperature is increased to 1850℃ at 3.5℃ / min and sintered at 0.8MPa for 4h.
[0085] The ultrathin silicon nitride ceramic substrate prepared in Example 2 has a thickness of approximately 0.182 mm, a thermal conductivity of 83.4 W / (m·K), a flexural strength of 986 MPa, a warpage of 0.27%, and a porosity of approximately 0.3%.
[0086] Example 3
[0087] S1 Pulping: 60 parts by weight of a compounded silicon nitride powder (0.3~0.4μm fine particle size powder and 0.7~0.8μm medium particle size powder in a mass ratio of 4:6), 8 parts by weight of a mixture of magnesium oxide, yttrium oxide and magnesium silicon nitride (magnesium oxide, yttrium oxide and magnesium silicon nitride in a mass ratio of 3:2:3), 1.5 parts by weight of a modified styrene-maleic anhydride copolymer (SMA and PPO compounded in a mass ratio of 5:5), and 19.5 parts by weight of toluene and anhydrous ethanol (toluene and anhydrous ethanol). Ethanol (mass ratio 3:7) was mixed and placed in a ball mill. 1 / 3 of the ball mill's internal volume of silicon nitride ceramic balls was added. After ball milling at 100 r / min for 10 h, a silicon nitride dispersion slurry was obtained. Then, 10 parts by mass of a biodegradable bio-based polymer binder (ethyl cellulose and cassava starch in a 5:5 ratio) and 3 parts by mass of tetraethyl orthosilicate were placed in the silicon nitride dispersion slurry. After ball milling at 120 r / min for 20 h, a silicon nitride slurry was obtained.
[0088] S2 Casting: After adjusting the viscosity of the silicon nitride slurry to 10000~13000 Pa·s, the casting process is carried out. A high-precision roll-to-roll casting machine is used for coating and forming. The casting substrate is a low-stress micro-embossed PET carrier tape. The wet film thickness is precisely matched to the green body thickness of about 0.135 mm. After casting and coating, it is pre-cured with 365 nm double-sided UV for 15~20 s. After pre-curing, the casting machine is set to five temperature zones with five gradient low-temperature drying at 30℃-40℃-50℃-60℃-80℃. The cast ceramic tape flows uniformly through each temperature zone at a speed of 1600 mm / h. After die-cutting, a low-stress ultra-thin green body with a thickness of about 0.135 mm and a size of about 245 mm × 185 mm is obtained.
[0089] S3 Debinding: Eleven sheets of 0.2mm high-purity graphite paper (ash content ≤300 ppm) were selected. A 10μm thick boron nitride coating was applied to both sides of nine sheets of graphite paper and one side of two sheets. Ten green blanks were alternately stacked with graphite paper, ensuring that both the top and bottom layers were graphite paper and that the contact surfaces between the green blanks and graphite paper had a boron nitride coating. This structure was placed in a double-layer porous boron nitride clamp, and nitrogen gas with an oxygen content of 500 L / min and an oxygen content of 500~800 ppm was introduced. The temperature was increased from room temperature to 220℃ at a rate of 2℃ / min and held for 50 min, then increased to 400℃ at a rate of 1.5℃ / min and held for 90 min, and then increased to 530℃ at a rate of 1.5℃ / min and held for 120 min. The furnace pressure was controlled at -10 Pa throughout the process. Debinding was performed under these conditions to obtain an ultrathin silicon nitride ceramic debinded blank.
[0090] S4 sintering: The crucible material is boron nitride with a porosity of 50%; the grain framework is constructed by heating from 30℃ to 1200℃ at 8℃ / min and holding at low pressure of 0.15MPa for 100min; then the temperature is increased to 1600℃ at 5℃ / min and held at 0.4MPa for 65min; then the temperature is increased to 1850℃ at 3℃ / min and sintered at 0.8MPa for 5h.
[0091] The ultrathin silicon nitride ceramic substrate prepared in Example 3 has a thickness of approximately 0.104 mm, a thermal conductivity of 83.8 W / (m·K), a flexural strength of 934 MPa, a warpage of 0.29%, and a porosity of approximately 0.2%.
[0092] Comparative Example 1
[0093] The difference between this comparative example and Example 1 lies in the pulping process at S1, specifically:
[0094] (1) Use silicon nitride powder with a single particle size of 0.5 μm;
[0095] (2) Use 8 parts by mass of a composite sintering aid of magnesium oxide and yttrium oxide (the mass ratio of magnesium oxide to yttrium oxide is 1:1);
[0096] (3) Use 1.5 parts by weight of castor oil instead of 1.5 parts by weight of modified styrene-maleic anhydride copolymer; use 3 parts by weight of phthalate instead of 3 parts by weight of tetraethyl orthosilicate;
[0097] Other technical solutions are the same as in Example 1.
[0098] In this comparative example, the silicon nitride ceramic substrate material has a thermal conductivity of 75.8 W / (m·K), a flexural strength of 726 MPa, a warpage of 0.23%, and a porosity of approximately 1.1%; its surface SEM characterization is as follows. Figure 3As shown, the microstructure exhibits a fine and fragmented pore distribution, with numerous micropore defects visible in the field of view, and a significant reduction in the number of large-sized, ultra-long columnar crystals. The average aspect ratio of the grains is small, resulting in low flexural strength. Furthermore, the green body obtained using the traditional slurry formulation exhibits insufficient uniform shrinkage during the binder removal and sintering process, leading to significant warping and failing to meet the application requirements of large-sized, ultra-thin silicon nitride substrates.
[0099] Comparative Example 2
[0100] The difference between this comparative example and Example 2 lies in the S2 casting process, specifically:
[0101] Comparative Example 2 did not use UV pre-crosslinking curing; it directly used hot air drying and substrate heating.
[0102] Other technical solutions are the same as in Example 2.
[0103] In this comparative example, the silicon nitride ceramic substrate material has a thermal conductivity of 80.2 W / (m·K), a flexural strength of 700 MPa, a warpage of 0.54%, and a porosity of approximately 0.9%. After casting, the green ceramic tape exhibits significant stress, causing it to curl towards the air surface, with slight ripples appearing on the air surface. Comparative Example 2 uses traditional hot air drying for casting; due to the thinness of the green ceramic tape, the solvent evaporates too quickly, leading to overall warping of the sintered ceramic sheet towards the air surface. The resulting ultrathin silicon nitride ceramic substrate cannot be bonded to the application products and cannot meet the application scenarios of large-size ultrathin silicon nitride substrates.
[0104] Comparative Example 3
[0105] The difference between this comparative example and Example 3 lies in the adhesive removal at S3, specifically:
[0106] Comparative Example 3 did not use graphite paper; instead, a 10 μm boron nitride coating was printed directly on the surface of the silicon nitride ceramic green body before it was stacked.
[0107] Other technical solutions are the same as in Example 3.
[0108] In this comparative example, the silicon nitride ceramic substrate material had a thermal conductivity of 81.4 W / (m·K), a flexural strength of 706 MPa, a warpage of 0.48%, and a porosity of approximately 1.2%. After sintering, numerous randomly distributed microscopic pits were found on the surface of the silicon nitride ceramic substrates. These pits were dot-shaped or short rod-shaped, and their size corresponded to the residual boron nitride crystal particles on the surface. Cross-sectional inspection confirmed that some pits penetrated the entire thickness of the substrate, forming penetrating holes. This defect appeared in multiple ceramic sheets sintered in stacks, exhibiting a batch-specific pattern. Even in products without penetrating voids and deep pits, approximately 20% of the ceramic sheets showed adhesion. Stable preparation of instant-fired ultrathin silicon nitride ceramic substrates was not possible.
[0109] The performance test results of Examples 1, 2, and 3 and Comparative Examples 1, 2, and 3 are shown in Table 1.
[0110] Table 1 Performance test results of the examples and comparative examples
[0111]
[0112] As can be seen from the above examples and comparative examples, this invention employs a coarse-fine bimodal submicron silicon nitride powder compound system, which effectively improves the solid content of the slurry and reduces the molding shrinkage rate. It utilizes a ternary bifunctional low-shrinkage organic system consisting of a biodegradable bio-based binder, a modified ceramic precursor plasticizer, and a low-volatility dispersant. Through precise component matching of the binder, plasticizer, and disperser phases, the total organic component content of the ultrathin silicon nitride slurry is strictly controlled at 12-16 wt%, solving the problems of high shrinkage, easy cracking, uneven dispersion, and concentrated degreasing gas generation in ultrathin green bodies. It also solves defects such as perforation, blistering, microcracks, and warping deformation caused by severe shrinkage in ultrathin green bodies of 0.200 mm and below. The invention employs a double-sided UV in-situ pre-curing + gradient low-temperature drying coupling process. Double-sided UV pre-curing suppresses the stress difference between the upper and lower surfaces caused by rapid solvent evaporation, preventing curling, wrinkling, and microcrack defects in ultrathin green bodies due to uneven drying rates. This invention uses an integrated large-size co-firing molding process, capable of producing thicknesses from 0.07 mm to 0.200 mm. The large-size ultra-thin silicon nitride ceramic substrate with a diameter of 190 mm × 138 mm and no subsequent grinding process is required. This avoids surface damage to the integrity of the silicon nitride grain structure caused by grinding, and significantly improves the long-term reliability and service life of the substrate.
Claims
1. A method for preparing an instant-fired ultrathin silicon nitride ceramic substrate, characterized in that: Includes the following steps: A. Slurry preparation: 50-65 parts by weight of compounded silicon nitride powder, 5-10 parts by weight of composite sintering aid, 0.5-3 parts by weight of dispersant, 13-25 parts by weight of organic solvent, 7-12 parts by weight of biodegradable bio-based polymer binder, and 2-7 parts by weight of plasticizer are ball-milled to obtain silicon nitride slurry; the compounded silicon nitride powder is a mixture of fine-particle-size powder (0.2-0.5 μm) and medium-particle-size powder (0.6-0.9 μm) at a mass ratio of 3-7:7-3; the composite sintering aid is a mixture of sintering aid A and sintering aid B, where sintering aid A is at least one of magnesium oxide, lanthanum oxide, yttrium oxide, aluminum oxide, gadolinium oxide, or lutetium oxide, and sintering aid B is at least one of magnesium silicon nitride or yttrium silicon carbonitride; the dispersant is a modified styrene-maleic anhydride copolymer. B. Casting: After adjusting the viscosity of the silicon nitride slurry, casting is performed. After completion, the upper and lower surfaces are pre-crosslinked and cured using an ultraviolet light source. After completion, segmented gradient low-temperature drying is used. The drying temperature is divided into multiple segments, gradually increasing from 30±3℃ to 80±5℃. The cast green ceramic tape flows through each temperature zone and is die-cut to obtain the green body. C. Glue Removal: Select N+1 sheets of graphite paper, coat both sides of N-1 sheets of graphite paper and one side of 2 sheets of graphite paper with a boron nitride coating, and alternately stack N green blanks with N+1 sheets of graphite paper, ensuring that the upper and lower layers of the green blanks are both graphite paper, and that the contact surfaces between the green blanks and the graphite paper have a boron nitride coating, and perform glue removal to obtain glue-removed blanks; N is an integer greater than or equal to 1; D. Sintering: The blank is subjected to gas pressure sintering under an inert atmosphere to obtain an instant-fired ultrathin silicon nitride ceramic substrate.
2. The method for preparing an instant-fired ultrathin silicon nitride ceramic substrate according to claim 1, characterized in that: At least one of the following must be met: In step A, sintering aid A is at least two of magnesium oxide, lanthanum oxide, yttrium oxide, aluminum oxide, gadolinium oxide, or lutetium oxide; In step A, sintering aid A accounts for 40% to 80% of the total mass of sintering aids, and sintering aid B accounts for 20% to 40% of the total mass of sintering aids. In step A, the particle size of sintering aid A is 0.05~0.5μm; In step A, the particle size of sintering aid B is 0.8~1.5μm; In step A, the organic solvent is a mixture of benzene and alcohol, wherein the benzene is at least one of benzene, toluene, xylene, or trimethylbenzene, and the alcohol is at least one of methanol, ethanol, propanol, butanol, pentanol, or hexanol; preferably, the organic solvent is a low-toxicity azeotropic system of benzene and alcohol in a mass ratio of 2~8:8~2; more preferably, the organic solvent is a mixture of ethanol and at least one of toluene or xylene in a mass ratio of 2~8:8~2. In step A, the modified styrene-maleic anhydride copolymer is a compound of SMA and PPO in a mass ratio of 3~7:7~3; In step A, the biodegradable bio-based polymeric binder is at least one of corn starch, tapioca starch, methylcellulose, and ethylcellulose; preferably, the biodegradable bio-based polymeric binder is at least two of corn starch, tapioca starch, methylcellulose, and ethylcellulose; more preferably, the biodegradable bio-based polymeric binder is a compound of at least one of corn starch or tapioca starch and at least one of methylcellulose or ethylcellulose; most preferably, the biodegradable bio-based polymeric binder is a compound of at least one of corn starch or tapioca starch and at least one of methylcellulose or ethylcellulose in a mass ratio of 2~8:8~2. In step A, the plasticizer is at least one of tetraethyl orthosilicate, PEG400, dioctyl adipate, or diisononyl cyclohexanedicarboxylate. In step A, during ball milling, silicon nitride ceramic balls occupying 1 / 4 to 1 / 2 of the ball mill volume are added.
3. The method for preparing an instant-fired ultrathin silicon nitride ceramic substrate according to claim 1, characterized in that: In step A, the compounded silicon nitride powder, composite sintering aid, dispersant and organic solvent are first ball-milled, and then biodegradable bio-based polymer binder and plasticizer are added for a second ball milling.
4. The method for preparing an instant-fired ultrathin silicon nitride ceramic substrate according to claim 1, characterized in that: At least one of the following must be met: In step A, the rotation speed of the ball mill for the first time is 80~150 rpm; In step A, the first ball milling time is 5h~20h; In step A, the rotation speed of the second ball mill is 80~150 rpm; In step A, the second ball milling time is 10h~30h.
5. The method for preparing an instant-fired ultrathin silicon nitride ceramic substrate according to claim 1, characterized in that: In step B, the drying temperatures are 2 to 4 of the following four temperatures: 30±3℃, 40±3℃, 50±3℃, 60±3℃, and 70±3℃, and 80±5℃.
6. The method for preparing an instant-fired ultrathin silicon nitride ceramic substrate according to claim 1, characterized in that: At least one of the following must be met: In step B, the viscosity of the silicon nitride slurry is adjusted to 5000~20000 Pa·s; In step B, the wavelength of the ultraviolet light source is 360±40nm; In step B, the pre-crosslinking curing time is 5~30s; In step B, the drying temperature is divided into 4 to 5 stages; In step B, the cast green ceramic tape flows uniformly through each temperature zone at a speed of 1600~2000 mm / h; In step B, the thickness of the green blank is 0.09~0.25mm; In step B, the dimensions of the green blank are 245mm × 185mm, with a dimensional tolerance of 1%.
7. The method for preparing an instant-fired ultrathin silicon nitride ceramic substrate according to claim 1, characterized in that: At least one of the following must be met: In step C, the thickness of the graphite paper is 0.2~1.2mm; In step C, the ash content of the graphite paper is ≤300ppm; In step C, the thickness of the boron nitride coating is 5~15μm; In step C, the debinding is carried out under an inert atmosphere; In step C, during glue discharge, the inert gas flow rate is 100~700L / min; In step C, during glue removal, the ambient oxygen content is 500~800ppm; In step C, during glue removal, the ambient air pressure is -5 to -10 Pa.
8. The method for preparing an instant-fired ultrathin silicon nitride ceramic substrate according to claim 1, characterized in that: In step C, during glue removal, the room temperature is raised to 220±20℃ and held, then raised to 400±40℃ and held, then raised to 600±60℃ and held; preferably, the heating rate from room temperature to 220±20℃ is 1~2℃ / min; preferably, the temperature is held at 220±20℃ for 30~60min; preferably, the heating rate from room temperature to 400±40℃ is 0.5~1.5℃ / min; preferably, the temperature is held at 400±40℃ for 60~90min; preferably, the heating rate from room temperature to 600±60℃ is 1~2℃ / min; preferably, the temperature is held at 600±60℃ for 60~180min.
9. The method for preparing an instant-fired ultrathin silicon nitride ceramic substrate according to claim 1, characterized in that: At least one of the following must be met: In step D, sintering is performed using a crucible made of boron nitride with a porosity of 25-50%. In step D, during sintering, the temperature is raised from 20-30℃ to 1100-1300℃ and held at 0.12-0.18 MPa, then raised to 1500-1700℃ and held at 0.3-0.55 MPa, then raised to 1800-1900℃ and sintered at 0.6-1.0 MPa; preferably, the heating rate from 20-30℃ to 1100-1300℃ is 5-8℃ / min; preferably... The temperature is maintained at 0.12~0.18MPa for 40~120min; preferably, the heating rate to 1500~1700℃ is 2~5℃ / min; preferably, the temperature is maintained at 0.3~0.55MPa for 60~180min; preferably, the heating rate to 1800~1900℃ is 2~5℃ / min; preferably, the temperature is sintered at 0.6~1.0MPa for 180~500min. In step D, the thickness of the resulting sintered ultrathin silicon nitride ceramic substrate is 0.07~0.20 mm.
10. A sinterable ultrathin silicon nitride ceramic substrate prepared by the preparation method according to any one of claims 1 to 9, characterized in that: Its flexural strength is ≥900 MPa, and its thermal conductivity is ≥80 W·m. -1 ·K -1 Warpage of 0.1% to 0.3%.